Child‐onset thrombotic thrombocytopenic purpura caused by p.R498C and p.G259PfsX133 mutations in ADAMTS13. (25th June 2018) - Schelpe, An‐Sofie; Orlando, Christelle; Ercig, Bogac; Geeroms, Chloë; Pareyn, Inge; Vandeputte, Nele; Velásquez Pereira, Leydi Carolina; Roose, Elien; Fostier, Karel; Nicolaes, Gerry A.F.; Deckmyn, Hans; De Meyer, Simon F.; et al.
Abstract: Introduction: Patients suffering from congenital thrombotic thrombocytopenic purpura (cTTP) have a deficiency in ADAMTS13 due to mutations in their ADAMTS13 gene. Objective: The aim of this study was to determine ADAMTS13 parameters (activity, antigen, and mutations), to investigate if the propositus suffered from child‐onset cTTP, and to study the in vitro effect of the ADAMTS13 mutations. Methods: ADAMTS13 activity and antigen were determined using the FRETS VWF73 assay and ELISA and ADAMTS13 mutations via sequencing of the exons. Mutant proteins were expressed in Chinese hamster ovary cells, and their expression was studied using fluorescence microscopy and ELISA. Molecular modeling was used to evaluate the effect of the mutations on ADAMTS13 structure and stability. Results: The propositus was diagnosed with cTTP at the age of 20. ADAMTS13 activity was below 10%, and 2 compound heterozygous mutations, the p.R498C point and the p.G259PfsX133 frameshift mutation, were identified. Expression of ADAMTS13 mutants revealed that the p.R498C and the p.G259PfsX133 mutation cause secretion and translation defects in vitro, respectively. Molecular modeling showed that the R498 intra‐domain interactions are lacking in the p.R498C mutant, resulting in protein instability. Conclusion: The ADAMTS13 mutations result in a severe ADAMTS13 deficiency explaining the patient's phenotype.